(untitled) (Journal of the Bangladesh Agricultural University, 2013)
An experiment was carried out to evaluate the performance of 22 lentil (Lens culinaris M.) genotypes for their yield and yield contributing characters at phenotypic level, relationship and diversity among the individuals and characterize the germplasm through phenotypic markers. ANOVA table revealed that significant variation was found among the genotypes for the characters plant height, days to maturity, number of primary branches plant-1, number of secondary branches plant-1, height of the lowest pod and 100-seed weight. Yield plant-1 was positively correlated with pods plant-1, seeds pod-1, seeds plant-1 and 100-seed weight. Considering yield plant-1 LM-123-7 was the best followed by LM-132-7, ICARDA-2348 and LM-13-1. Days to flowering, days of maturity and 100-seed weight showed high heritability. Path analysis revealed that pods plant-1 and 100-seed weight had positive direct effects on yield plant-1. The genotypes were grouped into five clusters based on Euclidean distance following Wards method and the highest intra-cluster distance was found in cluster IV and inter-cluster distance between the cluster IV and cluster V. Study of selection indices through discriminate functions observed that LM-123-7 ranked as the best followed by LM-132-7, LM-21-6, LM-24-3 and LM-14-2 and suggests that the highest scoring genotypes might be recommended for farmers cultivation for better yield. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14682 J. Bangladesh Agril. Univ. 10(2): 197-204, 2012